2019
DOI: 10.1016/j.jelekin.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Arm posture influences on regional supraspinatus and infraspinatus activation in isometric arm elevation efforts

Abstract: This study aimed to evaluate the effect of arm posture on activation of the anterior and posterior regions of supraspinatus and the superior and middle regions of infraspinatus during resisted isometric arm elevations.Thirty-one healthy participants performed eighteen isometric resistance exertions against a robotic arm in three elevation planes (flexion, scaption, abduction) and three elevation angles (30°, 90°, 150°) in maximal and sub-maximal resistance conditions. EMG data were obtained using fine wire ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…he modulation of infraspinatus (IS) muscle activity has been identified in a variety of intervention exercises for injury prevention. [1][2][3]9,24,28 However, professional tennis players present with IS atrophy syndrome to which the cause is uncertain. 31 Another shoulder external rotator muscle, the teres minor (TMi) muscle, generates up to 45% of external rotation (ER) force compared with the IS muscle.…”
mentioning
confidence: 99%
“…he modulation of infraspinatus (IS) muscle activity has been identified in a variety of intervention exercises for injury prevention. [1][2][3]9,24,28 However, professional tennis players present with IS atrophy syndrome to which the cause is uncertain. 31 Another shoulder external rotator muscle, the teres minor (TMi) muscle, generates up to 45% of external rotation (ER) force compared with the IS muscle.…”
mentioning
confidence: 99%
“…These results coincide with the activity values in the middle partition observed in our study. Some investigators measured independent activation of those partitions using EMG, and concluded that the muscle partitions have different roles [ 1 , 2 , 4 , 14 ]. However, EMG measurements from the partitions were not obtained during scaption, rather during specific positions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…empty can test. On the other hand, Alenabi et al 2019 [ 2 ] measured EMG in the superior and middle partitions of the ISP muscle at 30°, 90°, and 150° during scaption and demonstrated that the activation of both the superior and middle partitions of the ISP muscle, with 50% maximal voluntarily contraction, increased with increasing angle. These results are not in line with those obtained in the current study for the middle partition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al subdivided the anterior and the posterior regions into superficial, middle and deep sub-regions each based on fiber bundle arrangement (8). EMG studies have evaluated the functions of the morphologically divided regions (11,12). EMG data were obtained from the anterior and posterior regions suggesting that the anterior region was a mover and the posterior region acted as stress control for the anterior region (11,12).…”
Section: Introductionmentioning
confidence: 99%